2017
DOI: 10.1039/c7ra01541k
|View full text |Cite
|
Sign up to set email alerts
|

MesoDyn prediction of a pharmaceutical microemulsion self-assembly consistent with experimental measurements

Abstract: In this work, for the first time a coarse-grained model in a mesoscopic dynamic (MesoDyn) simulation for a pharmaceutical nonionic surfactant Brij97 was presented. By using this coarse-grained model, the morphology transition from oil in water (O/W) to a bicontinuous microemulsion formed in the Brij97/isopropanol/isoamyl acetate/H 2 O quaternary system was predicted. Furthermore, the effect of emulsifier/isoamyl acetate mass ratio, Brij97/alcohol mass ratio and alcohol structure on the droplets size and kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…37 In addition, the MesoDyn simulation could obtain the free energy change of the system, which could reect the system stability. 35 As shown in Fig. S6b, † rstly, the free energy of the system was decreased quickly (stage I), and then increased sharply in a split second when a steady shear g (g ¼ 5 Â 10 5 s À1 ) was introduced (stage II).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…37 In addition, the MesoDyn simulation could obtain the free energy change of the system, which could reect the system stability. 35 As shown in Fig. S6b, † rstly, the free energy of the system was decreased quickly (stage I), and then increased sharply in a split second when a steady shear g (g ¼ 5 Â 10 5 s À1 ) was introduced (stage II).…”
Section: Resultsmentioning
confidence: 91%
“…32,33 For example, the mesoscopic dynamics (MesoDyn) simulation method, which is based on dynamic mean-eld density functional theory (DFT), 34 is a powerful analytical approach. 35 It has recently been extensively applied in investigating the synthetic mechanism of porous materials. For instance, Zhang et al 36 had utilized the MesoDyn simulation method to simulate the microphase behavior of a triblock copolymer (P65) in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…349 In the meantime, Zhao et al focused on the droplet size and the kinetic formation process of oil in water microemulsions formed in the Brij97/2propanol/isoamyl acetate/H 2 O quaternary system by performing 10 μs CGMD simulations (Figure 28B). 347 Chatzidaki et al demonstrated, from 85 μs (!) CGMD, that encapsulated hydroxytyrosol and gallic acid antioxidants into reverse micelle composed of lecithin, monoglyceride, and water in triglyceride spontaneously self-assemble when starting from amorphous initial mixture conformations (Figure 28C).…”
Section: F F Tsmentioning
confidence: 99%
“…As the computers developing faster and faster, the molecules dynamics simulation has become an efficient tool for the investigation of the performance of surfactant solution [17] . As a mesoscale simulation algorithm, the dynamic mean field density functional method (MesoDyn) is proposed and has successfully been used to investigate the density distribution of various surfactant solutions [18][19][20][21][22] . MU et al put this simulation method into studying the self-assembled morphologies of polyelectrolytes [23] .…”
Section: Introductionmentioning
confidence: 99%